ANALYSIS OF DECISION MAKING FACTORS FOR ORDERING OUTDOOR ADVERTISING PRODUCT SERVICES THROUGH MARKETPLACE AT CV CANDIKARYA SEMARANG - Rita Andini; Rekno Sulandjari; Sri Praptono (SEAN Institute, 2022)
Along with the increasing growth in the world of advertising in Indonesia, consumer awareness of guarantees from advertising agencies or partner companies to produce advertising media that producers want is also increasing. This phenomenon has caused orders for outdoor advertising product services in Indonesia to also increase. This study analyzes the decision factors for ordering outdoor advertising product services on the Facebook platform in the marketplace feature to get products easily without going to a location, so that the negotiation process is more effective and efficient. Finally, make a decision to order the outdoor advertising product services. With the development of internet technology, the ways of communicating and negotiating in the business field have changed. The process of communication and negotiation by utilizing internet media, one of which is by using E-commerce. E-commerce is the process of buying and selling through internet media that is able to streamline time, making it relatively easier. The role of e-commerce has a positive impact, one of which is ordering outdoor advertising products to CV Candi Karya to get cheaper prices. In the beginning, as a means of communication, Facebook is starting to upgrade by adding features to its application, namely the marketplace, where users can communicate as well as order the desired outdoor advertising product. The purpose of this research is to: (1) identify the characteristics of respondents, (2) analyze the decision process for ordering outdoor advertising products, and (3) analyze the decision factors for ordering outdoor advertising products through marketplaces. The sampling method used is total sampling with snowball sampling technique. Analysis was carried out by descriptive analysis, factor analysis, crosstab analysis, and Net Promoter Score (NPS). Based on the results of the study, three groups of new factors formed the decision to order outdoor advertising products through the marketplace, namely individual factors, self-concept and socio-culture. The NPS value for outdoor advertising at CV Candi Karya was obtained by 45%, which means that there are more respondents who recommend it to the community than respondents who do not want to recommend it.